PENGAMBILAN KEPUTUSAN ATAS PESANAN KHUSUS BERDASARKAN PERHITUNGAN BIAYA RELEVAN - Nurkhaliza Richsandianti; Sunanto Sunanto; Kartika Rachma Sari (Politeknik Negeri Sriwijaya, 2021)
This study aims to analyze the relevant cost calculations for special orders for products, the 2017 farewell medal, the 2018 award statue, and the 2019 aklirik plaque. The problem that occurs is that the company does not properly classify production costs. The company also has not included electricity expense, building rent expense, and depreciation expense in the cost of production. The company also has not calculated relevant costs, which resulted in the management being incorrect in making decisions. To solve the above problems, the authors conducted a classification analysis of raw materials, labor, and factory overhead costs. The author also calculates relevant costs using differential analysis to determine whether management's decision to reject or accept orders is correct. Based on the analysis of the above problems, it is concluded that the company's decision to accept special orders is right for receiving orders